Women workers in male dominated industrial manufacturing organisations: Contrasting workplace case studies from Australia - John Burgess; Lindy Henderson; Glenda Strachan (Management Revue, 2005)
This study compared women's roles, expectations and experiences in two comparable, male dominated industrial manufacturing companies in Australia. Both organisations are subject to legislated equal opportunity program and reporting requirements. The research was conducted to examinee the differences between what is submitted in their EEO reports and the experience of women workers in the organisations. Good jobs and poor jobs existed in the same legislative and industrial framework and in the same local labour market. The differences are located in a combination of organisational and cultural conditions.
Keywords: 650; equal employment opportunity; job quality; human resources management; workplace culture; Weibliche Arbeitskräfte; Arbeitsmarktdiskriminierung; Personalmanagement; Verarbeitendes Gewerbe; Australien